2021
DOI: 10.1002/smll.202006839
|View full text |Cite
|
Sign up to set email alerts
|

[Cu15(PPh3)6(PET)13]2+: a Copper Nanocluster with Crystallization Enhanced Photoluminescence

Abstract: Due to their atomically precise structure, photoluminescent copper nanoclusters (Cu NCs) have emerged as promising materials in both fundamental studies and technological applications, such as bio‐imaging, cell labeling, phototherapy, and photo‐activated catalysis. In this work, a facile strategy is reported for the synthesis of a novel Cu NCs coprotected by thiolate and phosphine ligands, formulated as [Cu15(PPh3)6(PET)13]2+, which exhibits bright emission in the near‐infrared (NIR) region (≈720 nm) and cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 59 publications
(81 reference statements)
0
69
0
Order By: Relevance
“…48 Similarly, Bakr et al synthesized Cu 15 with CIEE. 49 CPL have a wide range of potential applications. 53 Feng et al reported 4-methylthiophenol-protected copper nanoclusterbased AIE particles and their application in β-galactosidase activity assay.…”
Section: ■ Introductionmentioning
confidence: 99%
“…48 Similarly, Bakr et al synthesized Cu 15 with CIEE. 49 CPL have a wide range of potential applications. 53 Feng et al reported 4-methylthiophenol-protected copper nanoclusterbased AIE particles and their application in β-galactosidase activity assay.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The as-prepared nanoclusters were successfully utilized to detect heparin by aggregation-induced quenching mechanism. Another study synthesized a near infrared emitting copper nanocluster co-protected by thiolate and phosphine ligands [ 47 ]. The structure of this nanocluster is atomically precise with the formula of [Cu 15 (PPh 3 ) 6 (PET) 13 ] 2+ .…”
Section: Preparation Methods and Sensing Mechanism Of Cu Ncsmentioning
confidence: 99%
“…The unique stability in ambient environment may be caused by the coordination effect between Cu and organic ligands, which then form dense organic protection shell to prevent the oxidation by O 2 in air. 56 In addition, intermolecular interactions including C-H•••π may also facilitate maintaining the crystallinities and stabilities. 57 Unfortunately, the intermediate Cu 15b isolated from CH 2 Cl 2 was unstable after being exposed to the air for hours, probably because that low boilingpoint and volatile CH 2 Cl 2 guest weakens the stability of the crystals.…”
Section: Beside Two Kinds Of μ 3 Bridging Modes (μmentioning
confidence: 99%
“…58,59 Page 13 of 26 CCS Chemistry that intermolecular C-H•••π interactions would substantially restrict the molecular rotations or vibrations and thus considerably enhance the radiative transitions in the crystalline state. 36,56,65 Isotropic temperature factor (Ueq) is a physical factor that reflects the thermal vibration level of atom in the crystal. 66 We also compared Ueq of C atoms between two isomers at 300K.…”
Section: Beside Two Kinds Of μ 3 Bridging Modes (μmentioning
confidence: 99%